Effects of classroom education on knowledge and attitudes regarding organ donation in ethnically diverse urban high schools - Cárdenas, Vicky (2010)
School-based health education is a promising approach for improving organ donation rates, but little is known about its efficacy among ethnically diverse youth. The impact of a classroom intervention was examined in a multicultural high school population where students’ ethnicities were 45% African American, 30% Asian American, and 33% Caucasian (allowing for multiracial choices). A baseline survey was administered to all health classes within 2 weeks prior to intervention. On the intervention day, classes randomly assigned to the intervention group received an educational session, followed by a second survey; in control classes, the second survey was taken before the educational session. At baseline, non-Caucasian ethnicity and male gender were each associated with lower levels of willingness to donate. Following the intervention, students in the intervention group demonstrated a significant increase in knowledge scores (p<0.001), as well as positive movement of opinion regarding willingness to donate (p<0.0001). Most importantly, the positive changes in opinion occurred independently of ethnicity and gender, in spite of these both being negative predictors of opinion at baseline. These results demonstrate that even a single classroom exposure can impact knowledge levels, correct misinformation, and effect opinion change on organ donation among an ethnically diverse adolescent population.